My boyfriend is a bear - Ribon, Pamela (Oni Press, 2018)
The delightful story of Nora who, after a succession of terrible boyfriends, finds a much happier relationship with a 500-pound American black bear. Bear meets girl. Nora has bad luck with men. When she meets an (actual) bear on a hike in the Los Angeles hills, he turns out to be the best romantic partner she's ever had! He's considerate, he's sweet, he takes care of her. But he's a bear, and winning over her friends and family is difficult. Not to mention he has to hibernate all winter. Can true love conquer all?